2021
DOI: 10.1200/jco.2021.39.15_suppl.e21167
|View full text |Cite
|
Sign up to set email alerts
|

Upfront thoracic radiotherapy to primary lession improve outcomes in patients with stage IV non-small cell lung cancer harboring EGFR mutations.

Abstract: e21167 Background: The role of thoracic radiotherapy in the treatment of metastatic EGFR mutant non-small cell lung cancer patients in literature datas are insufficient.The aim of this study was to examine the effectiveness of upfront thoracic radiotherapy in metastatic EGFR mutant NSCLC patients treated with chemotherapy or TKI. Methods: This study was designed as a hospital-based retrospective observational case-series study. A total of 141 patients with metastatic EGFR mutant non-small cell lung cancer who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The median time to progression (TTP) of radiation disease is 20.5 months; ORR is 50%; disease control rate (DCR) is 100%; and toxicity is acceptable (10% of patients develop rash; 20% of patients develop radiation pneumonia) (20). A retrospective study reached similar conclusions and also found that patients receiving stereotactic body radiation therapy (SBRT) had better OS compared to threedimensional conformal radiotherapy (46 months vs 26 months, P=0.05) (21). A prospective phase II Randomized controlled trial (NCT03595644) using SBRT combined with EGFR-TKI found that compared with EGFR-TKI alone, it prolonged the PFS (17.6 months vs 9.0 months, HR=0.52, P=0.016) and OS (33.6 months vs 23.2 months, HR=0.53, P=0.026) of patients, and reduced the incidence of grade 2 AE (45.2% vs 50%).…”
Section: Egfr-tki Combined With Radiotherapy 21 First Generation Egfr...mentioning
confidence: 79%
“…The median time to progression (TTP) of radiation disease is 20.5 months; ORR is 50%; disease control rate (DCR) is 100%; and toxicity is acceptable (10% of patients develop rash; 20% of patients develop radiation pneumonia) (20). A retrospective study reached similar conclusions and also found that patients receiving stereotactic body radiation therapy (SBRT) had better OS compared to threedimensional conformal radiotherapy (46 months vs 26 months, P=0.05) (21). A prospective phase II Randomized controlled trial (NCT03595644) using SBRT combined with EGFR-TKI found that compared with EGFR-TKI alone, it prolonged the PFS (17.6 months vs 9.0 months, HR=0.52, P=0.016) and OS (33.6 months vs 23.2 months, HR=0.53, P=0.026) of patients, and reduced the incidence of grade 2 AE (45.2% vs 50%).…”
Section: Egfr-tki Combined With Radiotherapy 21 First Generation Egfr...mentioning
confidence: 79%
“… 15 , 30 , 31 Moreover, several studies have examined the activity of thoracic radiation in advanced NSCLC patients harboring TKI-sensitive EGFR mutations. 22 , 23 , 32 , 33 Zheng et al conducted a prospective study to assess the efficacy of thoracic radiotherapy in combination with EGFR-TKIs on stage IV EGFR mutant lung adenocarcinomas. 22 A superior 1-year PFS was observed in the combination therapy group.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, limited studies address the efficacy and safety of adding thoracic radiotherapy to EGFR-TKIs as the first-line treatment for metastatic NSCLC patients with EGFR-sensitizing mutations. 22,23 In a recent prospective study involving 10 advanced NSCLC patients, Zheng et al reported that the concurrent EGFR-TKIs combined with thoracic radiotherapy achieve significant control for the primary lung lesions. 22 The data still need to be confirmed in a larger sample study.…”
Section: Introductionmentioning
confidence: 99%